2014
DOI: 10.1128/iai.01558-13
|View full text |Cite
|
Sign up to set email alerts
|

Children with Invasive Staphylococcus aureus Disease Exhibit a Potently Neutralizing Antibody Response to the Cytotoxin LukAB

Abstract: c Despite the importance of Staphylococcus aureus as a common invasive bacterial pathogen, the humoral response to infection remains inadequately defined, particularly in children. The purpose of this study was to assess the humoral response to extracellular staphylococcal virulence factors, including the bicomponent leukotoxins, which are critical for the cytotoxicity of S. aureus toward human neutrophils. Children with culture-proven S. aureus infection were prospectively enrolled and stratified by disease t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 51 publications
(55 citation statements)
references
References 42 publications
3
52
0
Order By: Relevance
“…However, like PVL, whether this antibody response to LukAB/HG alone is capable of conferring protection against infection with S. aureus remains to be determined. In this study, the titers of LukAB/HG antibody were higher than those of any other leucocidin tested, implying that it may be a dominant antigen seen during infection (330).…”
Section: Targeting Of Leucocidins As a Therapeutic Modalitymentioning
confidence: 89%
See 1 more Smart Citation
“…However, like PVL, whether this antibody response to LukAB/HG alone is capable of conferring protection against infection with S. aureus remains to be determined. In this study, the titers of LukAB/HG antibody were higher than those of any other leucocidin tested, implying that it may be a dominant antigen seen during infection (330).…”
Section: Targeting Of Leucocidins As a Therapeutic Modalitymentioning
confidence: 89%
“…In an additional study of children with S. aureus infection, it was found that those with invasive disease generated a high-titer antibody response to LukAB/HG. The antibodies generated have significant neutralizing capabilities in vitro (330). However, like PVL, whether this antibody response to LukAB/HG alone is capable of conferring protection against infection with S. aureus remains to be determined.…”
Section: Targeting Of Leucocidins As a Therapeutic Modalitymentioning
confidence: 99%
“…This toxin appears to be encoded in most sequenced strains of S. aureus [7, 90], yet another study noted that three out of ten clinical isolates failed to express LukAB protein [9]. Higher titers of LukAB neutralizing antibodies were found in convalescent patient sera compared to that of acutely ill patients in the setting of pediatric invasive S. aureus , indicating that LukAB is produced during human disease [91]. …”
Section: Overviewmentioning
confidence: 99%
“…S. aureus virulence relies, in part, on the production of a group of cytolytic toxins 10 including alpha-hemolysin and the bicomponent leukotoxins, notably Panton-Valentine leukocidin (PVL) and the recently described LukAB 11,12 . Recent work from our group demonstrated that invasive staphylococcal infection elicits a functional and potent humoral response to LukAB 13 . Data regarding the adaptive response to S. aureus in children with CF are limited, and the antibody response to key staphylococcal antigens, particularly those with vaccine or therapeutic potential, remains largely unknown 14-16 .…”
Section: Introductionmentioning
confidence: 99%